The role of parents in supporting sports achievement in football school students in 15 SSB - Anas Ardiansyah; Sumaryanto Sumaryanto; Komarudin Komarudin; Ibnu Khaldun Sudirman; Muhamad Ichsan Sabillah; Ruben Alexander Pakpahan; Fiky Zarya (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2023)
The role of parents in supporting the sports achievements of football school students in Sleman Regency is relatively lacking, creating potential inhibition in improving the achievements of these young athletes. This study aims to determine how big the role of parents in supporting sports achievement in football school students in 15 football schools in Sleman Regency and find out the coach's views on the support provided by parents to children in improving achievement. The method used is mix methods, the first sample is all parents/guardians of SSB members in Sleman Regency totaling 290 people. The second sample was all SSB trainers in Sleman Regency totaling 15 people. All data was retrieved using simple random sampling techniques. Data collection instruments using observation, interviews, and questionnaires. Data analysis uses descriptive analysis expressed in the form of percentages. The results showed that the large role of parents in supporting sports achievement in football school students in 15 football schools in Sleman Regency was in the category of